Analysis of project success factors in construction industry - Gunduz, Murat; Yahya, Ahmad Mohammed Ali (Technological and Economic Development of Economy, 2018)
A great emphasis has taken place to identify and analyse the factors that have been affecting the success and the failure of construction projects in recent decades. As a project-based industry, construction has heavily invested in such research. Moreover, the construction industry suffers the most to meet deadlines and budgets limits. The objective of this paper is to identify the critical success factors in construction industry. The study focused on Middle East region. In order to achieve this objective, 25 project success factors were identified by reviewing related literature. The factors were assessed for their impact and contribution to the actual performance of the project on three criteria: schedule, cost, and quality. Then a questionnaire was developed and sent to different experts in the construction industry. The collected data of 111 responses was then analysed statistically by using different tools such as: importance index, Spearman’s rank correlation factor and T-test. As a result, company’s technical capacity and scope and work definition were ranked the most important factors. The results of this research may provide a great assistance to professionals and researchers in identifying the critical factors in the construction industry.First published online 28 December 2015